(untitled) (Al-Aasar, 2025)
This study explores the power of electables locally influential political actors in shaping electoral outcomes in Pakistan’s hybrid political system. Using qualitative methods, including semi-structured interviews with political workers and voters, constituency-level case studies, and thematic analysis of party narratives, the research investigates how electables leverage biradari networks, patronage resources, and informal relationships with state institutions to consolidate political support. Findings indicate that electoral success in many regions is less dependent on party ideology and more closely tied to the electable’s ability to provide access to state services, mediate local conflicts, and secure development resources. The study also reveals how political parties strategically recruit electables to strengthen their chances in competitive constituencies, thereby reinforcing personalized, rather than programmatic, politics. Overall, the research highlights the continued dominance of electables in Pakistan’s electoral landscape and underscores how this dynamic shapes voter behavior, reconfigures party strategies, and limits the institutionalization of democratic politics.